Childhood maltreatment, personality vulnerability profiles, and borderline personality disorder symptoms in adolescents. (26th August 2022) - Marchetti, Daniela; Musso, Pasquale; Verrocchio, Maria Cristina; Manna, Giovanna; Kopala-Sibley, Daniel C.; De Berardis, Domenico; De Santis, Sandro; Falgares, Giorgio
Abstract: Adverse childhood experiences are significant risk factors in the development of adolescent borderline personality disorder symptoms (BPDs). Theorists have posited that two personality vulnerabilities factors, self-criticism and dependency, may inform our understanding of this relationship. However, no research has examined the associations between early negative experiences, personality vulnerabilities, and adolescent BPDs. The current study aimed to identify profiles of dependency and self-criticism to examine the associations of these profiles with cumulative forms of childhood maltreatment (CM) and BPDs as well as to explore the mediating and moderating role of vulnerable personality profiles in the relationship between cumulative CM and BPDs. Two hundred and forty-one nonclinical and clinical adolescents participated in the study ( Mage = 16.37, SD = 1.84). The findings indicated three different profiles: average dependent profile, dependent and self-critical profile, and self-critical profile. Individuals in the average dependent profile presented lower levels of CM and BPDs. Mediation analyses showed that relative to the average dependent profile, a higher cumulative CM history predicted a higher probability of belonging in the dependent and self-critical profile or the self-critical profile and, in turn, this was associated with higher levels of BPDs. No moderating effects of profiles of dependency and self-criticism were found.